Ladders and stairs: how the intervention ladder focuses blame on individuals and obscures systemic failings and interventions - Paetkau, Tyler (Journal of medical ethics, 2024)
Introduced in 2007 by the Nuffield Council on Bioethics, the intervention ladder has become an influential tool in bioethics and public health policy for weighing the justification for interventions and for weighing considerations of intrusiveness and proportionality. However, while such considerations are critical, in its focus on these factors, the ladder overemphasises the role of personal responsibility and the importance of individual behaviour change in public health interventions. Through a study of vaccine hesitancy and vaccine mandates among healthcare workers, this paper investigates how the ladder obscures systemic factors such as the social determinants of health. In overlooking these factors, potentially effective interventions are left off the table and the intervention ladder serves to divert attention away from key issues in public health. This paper, therefore, proposes a replacement for the intervention ladder—the intervention stairway. By broadening the intervention ladder to include systemic factors, the stairway ensures relevant interventions are not neglected merely due to the framing of the issue. Moreover, it more accurately captures factors influencing individual health as well as allocations of responsibility for improving these factors.